AKAR TERORISME DALAM ISLAM? - Sukendar Sukendar (Jurnal Theologia, 2012)
Terrorism has been a popular issue since September the Eleven. The incident was followed by a proclamation of war against terrorism by the US governments. The US invited other countries to join the campaign with President George W. Bush's monumental saying "You are either with us or against us". The effort of countering terrorism by the US and other countries with a weapon is likely to be ineffective. Countering terrorism, especially religious motivated terrorism can effectively be conducted by understanding the root causes of terrorism and eliminating what so-called global injustice.Terorisme menjadi isu populer sejak 11 September (2001). Insiden ini diikuti dengan sebuah proklamasi perang melawan terorisme oleh pemerintah USA. USA mengajak negara-negara lain untuk bergabung kampanye dengan perkataan monumental Presiden George W. Bush, ”Anda bersama kami, atau melawan kami.” Usaha menghadapi terorisme oleh USA dan negara-negara lain dengan senjata tampaknya tidak efektif. Melawan terorisme, khususnya terorisme yang dimotivasi oleh agama, bisa efektif dilakukan dengan memahami akar penyebab terorisme dan mengeliminasi apa yang disebut ketidakadilan global